2010
DOI: 10.1111/j.1365-2486.2009.02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon bio‐sequestration within the phytoliths of economic bamboo species

Abstract: The rates of carbon bio-sequestration within silica phytoliths of the leaf litter of 10 economically important bamboo species indicates that (a) there is considerable variation in the content of carbon occluded within the phytoliths (PhytOC) of the leaves between different bamboo species, (b) this variation does not appear to be directly related to the quantity of silica in the plant but rather the efficiency of carbon encapsulation by the silica. The PhytOC content of the species under the experimental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
205
6
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(219 citation statements)
references
References 29 publications
4
205
6
4
Order By: Relevance
“…Studies on wheat phytoliths have also demonstrated that there was no relationship between phytolith yield and percentage PhytOC content on a dry weight basis (P = 0.047, R 2 = 0.075) and a strong correlation also existed between percentage PhytOC content on a dry weight basis and the occluded carbon content of the phytoliths themselves [42]. These results all show that percentage PhytOC content on a dry weight basis is not determined by phytolith yield, but by the efficiency of carbon trapping during the phytolith's deposition in plant [19]. In other work, phytoliths could not be decomposed by using conventional methods of measuring soil carbon such as dry combustion and wet oxidation [43,44].…”
Section: Phytoliths and Phytocsupporting
confidence: 54%
See 2 more Smart Citations
“…Studies on wheat phytoliths have also demonstrated that there was no relationship between phytolith yield and percentage PhytOC content on a dry weight basis (P = 0.047, R 2 = 0.075) and a strong correlation also existed between percentage PhytOC content on a dry weight basis and the occluded carbon content of the phytoliths themselves [42]. These results all show that percentage PhytOC content on a dry weight basis is not determined by phytolith yield, but by the efficiency of carbon trapping during the phytolith's deposition in plant [19]. In other work, phytoliths could not be decomposed by using conventional methods of measuring soil carbon such as dry combustion and wet oxidation [43,44].…”
Section: Phytoliths and Phytocsupporting
confidence: 54%
“…However, far fewer studies have examined the PhytOC content of different plants. Although there already have been some studies on the PhytOC content of bamboo and sugarcane [19,38], to date, very little is known about other higher silicon accumulating plants, such as Sorghum bicolor, Oryza sativa, Panicum miliaceum and Setaria italica.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As Santos et al (2012) stress, this is an important issue as the variations in PhytOC yield between different plant types and even cultivars of the same crop are increasingly being looked to as an approach with potential for enhancing carbon biosequestration in agriculture and forestry (e.g. Sullivan, 2005, 2011;Parr et al, 2009Parr et al, , 2010Jansson et al, 2010;Zuo and Yuan, 2011;Song et al, 2012). However, to suggest solely on the basis of morphology in SEM images published elsewhere that phytolith extraction techniques they did not examine (such as the microwave digestion technique) "seem" unable to extract extraneous carbon is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately quantifying the phytC is important for the assessment of its significance in the terrestrial C cycle. Multiple studies have recently claimed that phytC may play a role in atmospheric CO 2 sequestration and climate change mitigation (Parr and Sullivan, 2005;Parr et al, 2010;Song et al, 2014;Huang et al, 2014;Li et al, 2014;Zuo et al, 2014), although the fluxes of phytC from vegetation to soils and the residence time of phytC in soils are still largely unknown. PhytC content as high as 20 % dry weight was obtained when using a phytolith extraction method based on microwave digestion (Parr and Sullivan, 2014).…”
Section: Introductionmentioning
confidence: 99%